Administrative Corruption and Integrity Violations in the Charter School Sector. (2nd January 2021) - Ertas, Nevbahar
Abstract : Charter school legislation permits new actors to compete for public funds to provide education to K-12 students across the United States. Proponents of market-oriented policies predict that privatization cuts costs and improves service quality, by removing bureaucracy and boosting creativity. These schools were predicted to become laboratories of innovation that would use their flexibility from state and local requirements to improve public education. This study suggests that the less regulated service systems may have also propagated an environment susceptible to managerial and accountability inadequacies, if not outright integrity violations and corruption. Using systematic document review and the existing literature on corruption in education, a typology of integrity violations and corruption in the charter school sector is developed in this paper. A better understanding of the characteristics of the institutional environment that enable corrupt behavior is necessary to develop effective strategies to prevent corruption, protect children, and manage public funds effectively.